Microfluidic fabric-based electrochemical device for detection of clinical analytes in physiological fluids [electronic resource] - Radha Swathe Priya Malon Marugan, 1987-, author (2014)
Thesis (Ph.D (Kejuruteraan Bioperubatan)) - Universiti Teknologi Malaysia, 2014